SALSA: SAving Lives Staying Active to Promote Physical Activity and Healthy Eating - Rebecca E. Lee; Scherezade K. Mama; Ashley Medina; Raul Orlando Edwards; Lorna McNeill (Hindawi Limited, 2011)
Physical inactivity, poor dietary habits, and obesity are vexing problems among minorities. SAving Lives, Staying Active (SALSA) was an 8-week randomized controlled crossover design, pilot study to promote regular physical activity (PA) and fruit and vegetable (FV) consumption as a means to preventing weight gain among women of color. Participants completed measures of demographics, PA, and dietary habits. Women (𝑁=50;𝑀=42 years) who participated were overweight (𝑀BMI=29.7 kg/m2; 𝑀bodyfat=38.5%) and reported low levels of leisure time PA (𝑀=10.7 MET-min/wk) and FV consumption (𝑀=4.2 servings/day). All were randomized to a four-week (1) semiweekly Latin dance group or (2) internet-based dietary education group. All participants reported a significant increase in weekly leisure time PA from baseline (𝑀=10.7 MET-min/wk) to follow up (𝑀=34.0 MET-min/wk, 𝑃<.001), and FV consumption increased over time by group (𝑃=.02). Data suggest that Latin dance interventions to improve PA and web-based interventions to improve dietary habits show promise for improving health among women of color.